"Evil with Gentle Hands and Pure Eyes": the Poetics of Outrage in the Novel "Serafima" by Oles Ulianenko - Король, Лідія (Київський національний університет імені Тараса Шевченка, 2025)
Background. At the turn of the millennium, somatic issues became highly relevant in the post-Soviet space. The prolonged prohibition of artistic self-expression, the control of the informational agenda, the denial of sexual life ("there was no sex in the Soviet Union"), and other prerequisites formed by the USSR's policies resulted in an artistic hyperfixation on the body. Perhaps most polarizing in Ukrainian literature is the representation of the body in the works of Oles Ulianenko: ranging from animalistic-repulsive to sexually attractive. The reflection on national ideas, the actualization of bodily issues, and the return of Oles Ulianenko to the public space together determine the relevance of this study. Despite the large number of works dedicated to the writer's oeuvre, scholars have largely overlooked the spiritual and bodily degradation of the characters in the novel "Serafima". Analyzing precisely these aspects allows one to interpret the text through the lens of outrage aesthetics and avoid moral judgment of the work – this defines the novelty of the study. Its aim is to trace the interrelation of bodily and spiritual degradation of the characters in Oles Ulianenko's "Serafima" and its realization as a marker of outrage aesthetics. Methods. The general scientific method of research was used, in particular synthesis and generalization. Also applied were poetic analysis and the method of receptive aesthetics. Results. The theoretical foundation of the study includes works by Yurii Bilodid, Iryna Ihnatenko, Felix Shteinbuk, and others, which allow for the consideration of spirituality, morality, and corporeality as interconnected categories. The emphasis is placed on a receptive approach to moral norms, which change depending on the social context. Particular attention is given to the connection between family upbringing and the heroine's degradation, which enables a new reading of the text in the context of postcolonial criticism. At the center of the study is the idea that the degradation of the characters on the level of intentions, actions, and bodily transformations is artistically motivated and aimed at shocking the reader. The article traces how outrage in "Serafima" functions not merely as provocation, but as a means of representing spiritual crisis and an attempt to critique traditional moral norms, especially those entrenched by the Soviet legacy. Conclusions. Outrage in the novel serves not as an end in itself, but as a tool of postcolonial reflection. It is proposed to interpret outrage as a form of artistic resistance – against the banality of evil, the stereotypical image of women, and the spiritual heritage of the Soviet era.

Вступ. У період зламу тисячоліть на пострадянському просторі актуалізувалися соматичні питання. Тривала заборона на мистецьке самовираження, контроль інформаційної повістки, заперечення сексуального життя ("в радянському союзі сексу не було") та інші передумови, сформовані політикою СРСР, вилилися в гіперфіксацію мистецтва на тілі. Чи не найбільш полярно в українській літературі тіло представлено у творах Олеся Ульяненка: від тваринно-огидного до сексуально-привабливого. Рефлексування національних ідей, актуалізація питань тілесності та повернення в публічний простір Олеся Ульяненка разом зумовлюють актуальність цієї розвідки. Попри велику кількість праць про творчість письменника, науковці оминули увагою духовну та тілесну деградацію персонажів у романі "Серафима". Аналіз саме цих аспектів допомагає трактувати текст крізь призму епатажу й уникнути моральної оцінки твору, що й визначає новизну цієї розвідки, а її мета – простежити взаємозвʼязок тілесної та духовної деградації героїв у романі Олеся Ульяненка "Серафима" та її втілення як ознаки епатажу. Методи. Використано загальнонауковий метод дослідження, зокрема синтез та узагальнення. Також застосовано постколоніальну критику, поетологічний метод і метод рецептивної естетики. Результати. У теоретичному підґрунті дослідження – праці Юрія Білодіда, Ірини Ігнатенко, Фелікса Штейнбука та інших, які дозволяють розглядати духовність, мораль і тілесність як взаємопов'язані категорії. Акцент зроблено на рецептивному підході до моральних норм, що змінюються залежно від суспільного контексту. Особливу увагу приділено зв'язку між сімейним вихованням та деградацією героїні, що дозволяє по-новому прочитати цей текст у контексті постколоніальної критики. У центрі розвідки – ідея, що деградація персонажів на рівні інтенцій, вчинків і тілесних трансформацій є художньо вмотивованою і спрямованою на епатування читача. У статті простежено, як епатаж у "Серафимі" працює не просто як провокація, а як спосіб відтворення духовної кризи та спроба критики традиційних моральних норм, особливо тих, що закріплені радянською спадщиною. Висновки. Епатаж у романі виступає не самоціллю, а інструментом постколоніальної рефлексії. Запропоновано трактувати епатаж як спосіб художнього спротиву – проти буденності зла, стереотипного образу жінки, духовного спадку радянської епохи.
"Зло з ніжними руками й чистими очима": поетика епатажу в романі Олеся Ульяненка "Серафима"
Keywords: постколоніалізм; епатаж; сучасна українська література; тілесність; postcolonialism; outrage aesthetics; contemporary Ukrainian literature; corporeality